Digital Transformation And Internal Communication In Improving Employee Performance: A Moderation Analysis Of Human Resource Competencies - Renika Gustian Fulialza; Dheo Rimbano; Sutanta Sutanta (UNIVED Press, 2026)
This study examines the effect of digital transformation and internal communication on employee performance, with human resource competence (HR) as a moderating variable at the Industry and Trade Office of Musi Rawas Regency. Using an explanatory quantitative approach, this study involved the entire ASN and non-ASN population of 53 employees through the saturated sample technique. Data collection instruments in the form of questionnaires were analyzed using SPSS, with regression and Moderated Regression Analysis (MRA) methods. The results showed that digital transformation and internal communication partially and simultaneously significantly affected employee performance. HR competence strengthens the relationship between the two independent variables of performance. The limitations of this study lie in the scope of a single organization and a limited sample size, so the results cannot be widely generalized. The findings provide a practical contribution to the public sector in designing technology and communication-based HR development strategies and enrich the literature on moderating variables' role in government organizations. This research is essential because of the integration of three key organizational elements, such as digital transformation, internal communication, and HR competencies, in one analysis model to improve employee performance.